The Influence of Digital Literacy, Independence, and Learning Motivation on Student Learning Effectiveness Through Self-Efficacy - Putri Mayang Sari; Aswardi Aswardi; Ta Ali Ta Ali; Oriza Candra; M Giatman (STKIP Singkawang, 2025)
In the era of digital transformation, vocational students are required to master not only technical skills but also digital competence, learning autonomy, and strong motivation. However, various challenges such as low digital literacy, limited learning independence, and fluctuating motivation levels hinder the effectiveness of learning processes in vocational schools. This study aims to examine the influence of digital literacy, learning independence, and learning motivation on learning effectiveness, with self-efficacy acting as a mediating variable. A quantitative approach using an explanatory survey method was applied to a sample of 197 vocational high school students selected through proportional stratified random sampling. Data were collected using a validated Likert-scale questionnaire and analyzed through Partial Least Squares Structural Equation Modeling (PLS-SEM). The results revealed that all three independent variables significantly affect learning effectiveness, both directly and indirectly through self-efficacy. Among them, self-efficacy demonstrated the strongest effect. The findings underscore the importance of enhancing students' self-efficacy to maximize the impact of digital literacy, autonomy, and motivation on learning outcomes. These results contribute to educational theory and practice by highlighting the mediating role of self-efficacy in vocational learning settings